Implementation of the Learning Program at the PGRI One-Roof Kindergarten Neglasari, Sukabumi Regency - Ely Yeni Hadiansyah; Nia Dewi Srikandi; Juriah; Ela; Ende sujana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to determine the implementation of the learning program in TK pgri satu atap neglasari. In detail, the objectives of this study are: (1) to determine the preparation of learning programs/plans, (2) to determine the implementation of learning programs, (3) to determine the evaluation of learning. This study uses a qualitative method, which reveals the data in the form of words from the informants and the objects studied as they are. To answer the research objectives, the data collection techniques in this study used interviews, observations, and document studies. While the analysis technique used is data reduction, data exposure and drawing conclusions. Then the data assurance technique consists of triangulation (cross checking), between methods and triangulation of data between informants. The implementation of the teaching program in TK pgri Satap Neglasari was carried out by three teachers as informants and observing 22 students in class B. There were three findings of this study, namely: First; The preparation of the learning program at the Pelangi Kualuh Hulu Kindergarten in Labura Regency has been prepared by the principal together with the teachers, as evidenced by the daily learning implementation plan, daily learning activity schedule, which also found support for the 4-day RPPH document. Second; The implementation of learning takes place in two study groups class A and class B which are managed by two teachers and one principal with pre-learning activities, initial learning activities, core learning activities, and closing activities. Third; learning evaluation is carried out at the closing time allocation as the final process to assess the student's achievement of the competencies specified as in the lesson plan.